From rare anomaly to clinical reality; managing venous thrombosis in the setting of congenital inferior vena cava agenesis - Hassanesfahani, Maryam; Bucci, Loryn; Griner, Stephens; Guerges, Mina (International Surgery Journal, 2024)
A congenital absence of the inferior vena cava (IVC) is a rare anomaly known to be linked with idiopathic deep venous thrombosis (DVT). This anomaly is more commonly observed in individuals with other congenital cardiac anomalies, with an incidence ranging from 0.6% to 2%. Here we are reporting a rare case of missing IVC presented with extensive bilateral lower extremity and iliac veins DVT. The symptoms responded well to therapeutic doses of heparin. In this article, we will review some other cases of IVC agenesis and different management including medical, interventional, and surgical approaches.